Integrating ICT with Drama Activities (European Journal of Teaching and Education, 2025)
As a teaching tool, drama contributes to the development of understanding the physical, emotional, intellectual, aesthetic, social, moral, and spiritual dimensions of human experience. Apart from developing communication skills, drama encourages confidence, self-esteem, cooperation, empathy, responsibility, problem-solving management, creativity, and imagination. The implementation of ICT should be used in a complementary way and not as a substitute for dramatic activities to create an empowering and enriching educational environment. The use of ICT implies the development and presentation of activity results, as well as hardware and/or software support for enhancing the drama environment. This paper presents a methodical scenario that purposefully incorporates ICT possibilities without disturbing the natural flow of drama activities.